2017
DOI: 10.1371/journal.pone.0173094
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of fungal accessory hemicellulases in Arabidopsis thaliana triggers transcriptional patterns related to biotic stress and defense response

Abstract: The plant cell wall is an abundant and renewable resource for lignocellulosic applications such as the production of biofuel. Due to structural and compositional complexities, the plant cell wall is, however, recalcitrant to hydrolysis and extraction of platform sugars. A cell wall engineering strategy to reduce this recalcitrance makes use of microbial cell wall modifying enzymes that are expressed directly in plants themselves. Previously, we constructed transgenic Arabidopsis thaliana constitutively express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…We also identified many transcription factors, in particular, several WRKY factors. Some of these genes were found similarly affected in Arabidopsis stems ectopically overexpressing PcGCE (Tsai et al, 2017), as shown in Table S9. The identified genes constitute transcriptional modules that likely operate in recognition of PcGCE and other molecular patterns associated with pathogens to activate defense systems in aspen.…”
Section: Transcriptomics Of Early Stages Of Leaf Development Identified Putative Receptors and Signaling Components Involved In The Percementioning
confidence: 90%
See 3 more Smart Citations
“…We also identified many transcription factors, in particular, several WRKY factors. Some of these genes were found similarly affected in Arabidopsis stems ectopically overexpressing PcGCE (Tsai et al, 2017), as shown in Table S9. The identified genes constitute transcriptional modules that likely operate in recognition of PcGCE and other molecular patterns associated with pathogens to activate defense systems in aspen.…”
Section: Transcriptomics Of Early Stages Of Leaf Development Identified Putative Receptors and Signaling Components Involved In The Percementioning
confidence: 90%
“…Similar to aspen, Arabidopsis expressing PcGCE exhibited transcriptomic changes typical of biotic stress responses, SA signaling (Tsai et al, 2017). Moreover, several biotic-stress related genes were affected in common in both species, including glutamate receptor GLR2.7, recently shown to constitute a core stress response gene (Bjornson et al, 2021), WRKY51 that mediates JA signaling inhibition by SA and low oleic acid levels (Gao et al, 2011), SOBIR1 that together with BAK1 and RLK23 recognizes NLP20 peptide inducing necrosis (Albert et al, 2015), and other genes which we identified as putative candidates for early PcGCE responses in aspen leaves (Table S9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the complexities of cell wall structure and signaling, it is difficult to pinpoint how pectin exerts control over these functions. Previous research has shown that constitutive expression of microbial hydrolases in the plant apoplast is a useful approach to investigate the impacts of cell wall post-synthetic modification on cell wall signaling, plant fitness, and stress responses [ 15 , 57 , 58 , 59 , 60 , 61 ]. Since plant growth is often halted under stress, this approach provides an opportunity to understand pectin’s contribution to both plant cell wall mechanics and plant response to stresses.…”
Section: Discussionmentioning
confidence: 99%